PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Ubabuddin Ubabuddin (Cross-border, 2018)
Supervision is not only aimed at controlling to see whether all activities have been carried out according to the plans or programs that have been outlined, but more than that. Supervision also pays attention to the state of the teacher's performance whether he is successful in teaching or not besides that supervision also pays attention to and helps the teacher in dealing with problems or weaknesses of the teacher in teaching so that he can be successful in teaching or educating. For this reason, supervision is carried out by the principal in improving teacher performance. Teacher performance is increasingly important when the institution will reposition. This means how the institution must know what factors affect teacher performance. The results of the analysis will be useful for making teacher HR development programs optimally and it is very necessary to advance the quality of education. Teachers need special attention from the government and society, therefore the government regulates the improvement of the quality of educators or teachers nationally through Law No. 20 of 2003 concerning the National Education System. In order to implement the law, the government issued PP No. 19/2004 on National Education Standards.